Análisis psicométrico del cuestionario de inteligencia emocional aplicado en adultos que trabajan en instituciones públicas y privadas de Arequipa - Walter L Arias Gallegos (2017)
In the present study we made a psychometrical analysis of the Emotional Intelligence Questionnaire in a sample of 162 people 20 and 62 aged (42.8% male and 57.2% female) from four organizations at Arequipa, two public, and other two private. The statistical analysis points that the items present an adequate homogeneity according to the item-test correlations, and the questionnaire has a three components structure: Self-knowledge, control and empathic ability, Inadequate management of emotions, and Negative Emotions. Moreover, we calculate the reliability of this instrument by mean of the Cronbach’s Alpha Test, which reports a coefficient of α = 0.733.